Jadwal Induk Produksi Thinner dengan Perhitungan RCCP Bill of Labor Approach dan Sistem Dinamis (Studi Kasus: Pabrik Produksi Thinner PT XY) - Ramdan, Asep; Hermawan, Asep; Oetomo, Dedy Setyo (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
PT. XY is one of the largest paint and coating material manufacturers in Asia. In addition to producing paint, the company also produces paint thinners. In its production process, the company faces difficulties in estimating the optimal production quantity for each period, often experiencing urgent processes, delivery delays, and even disruptions to the production process due to sudden schedule changes. This research will use the Exponential Smoothing forecasting method to predict demand in the coming period. A Master Production Schedule (MPS) calculation was also performed, which was then followed by RCCP. This method is used to compare production needs with the company's available capacity. The Master Production Schedule (MPS) that can be planned at PT. XY for 1 year from January 2025 – December 2025 is 7,926,032 Liters, produced by 32 people each month with a UPRT of 7,421,324 Liters and a Safety Stock of 33,025 Liters per month, with respective proportions of 61% IU products, 8% TIU products, and 31% SEMI products.